29.9k views
1 vote
Please solve this, will rate 5 stars and mark as STAR!​

Please solve this, will rate 5 stars and mark as STAR!​-example-1

1 Answer

2 votes

Answer:


\boxed{5 \cdot √(2) \cdot \sqrt[6]{5} }

Explanation:


\sqrt[3]{250} \cdot \sqrt{\sqrt[3]{10} }


\sqrt{\sqrt[3]{10} } \implies (10^(1)/(3) )^(1)/(2) =10^(1)/(6) =\sqrt[6]{10}


\therefore \sqrt{\sqrt[3]{10} }=\sqrt[6]{10}


\text{Solving }\sqrt[3]{250} \cdot \sqrt{\sqrt[3]{10} }


250=2 \cdot 5^3


\sqrt[3]{250}=\sqrt[3]{2\cdot 5^3}=5 \sqrt[3]{2}

Once


\sqrt[6]{2} \cdot \sqrt[6]{5} = \sqrt[6]{10}

We have


5 \sqrt[3]{2} \cdot \sqrt[6]{2} \cdot \sqrt[6]{5}

We can proceed considering the common base of exponentials


\sqrt[3]{2} \cdot \sqrt[6]{2} = 2^{(1)/(3)} \cdot 2^{(1)/(6) } = 2^{(3)/(6) } = 2^{(1)/(2) }=√(2)

Therefore,


5 \sqrt[3]{2} \cdot \sqrt[6]{2} \cdot \sqrt[6]{5} = 5 \cdot √(2) \cdot \sqrt[6]{5}

User Anthonycr
by
5.1k points